The Role of The Alternative Financial Market in Financial SMEs: Tunisia Case Study - TALHI, Samah; AOUAM, Nesrine; BAALOUL, Naoufel (Journal of Human Sciences, 2020)
The absence of effective financial intermediation which supplies the small and medium enterprises with long-term funds as well as limited banking services, have led to the urgent need to establish alternative financial market for securities directed specifically to these institutions, Especially after the main complications found in the first market because of the long and costly procedures and the difficult conditions that small and medium enterprises face when they want to enroll. The alternative financial market is considered as a modern and effective means of financing proven in many countries like Tunisia, because of their attractiveness to investments and mobilization of savings to face the funding request that needs the sector of small and medium enterprises with the necessary amounts, low costs and in the appropriate time.